1995
DOI: 10.1161/01.cir.91.12.2904
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coronary Artery Distensibility by Intravascular Ultrasound

Abstract: These results suggest that coronary distensibility is impaired in the coronary sites accompanying occult atherosclerosis, none of which can be detected by the conventional angiography. NTG can augment coronary distensibility in the segments without a markedly thickened intima-media complex. We suggest that thickness of the intima-media complex can contribute to determining the coronary distensibility in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 33 publications
2
35
1
1
Order By: Relevance
“…Atherosclerosis also has been implicated in the alteration of the pulsatile characteristics of blood vessels. 39,40 However, the relation between altered mechanical properties of blood vessels and atherosclerosis is complex and probably involves both structural and functional influences that have led to conflicting reports in the literature. 41 An attractive hypothesis consistent with the data are that altered endothelial function is at the root of the large and small artery compliance reduction with aging.…”
Section: Figurementioning
confidence: 99%
“…Atherosclerosis also has been implicated in the alteration of the pulsatile characteristics of blood vessels. 39,40 However, the relation between altered mechanical properties of blood vessels and atherosclerosis is complex and probably involves both structural and functional influences that have led to conflicting reports in the literature. 41 An attractive hypothesis consistent with the data are that altered endothelial function is at the root of the large and small artery compliance reduction with aging.…”
Section: Figurementioning
confidence: 99%
“…In this regard, recent studies have demonstrated that coronary distensibility is impaired in coronary sites with occult atherosclerosis.14. 30 In fact, using IVUS atherosclerosis is nearly ubiquitous in angiographically normal proximal reference segments.30 Therefore, theoretically speaking, it could be suggested that angiographically silent disease may contribute to the difficulties encountered by the catheter in negotiating the proximal coronary segments. Nevertheless, in the present study, we were unable to demonstrate any relationship between the presence of proximal disease by JVUS and the likelihood of successful imaging.…”
Section: Present Studymentioning
confidence: 99%
“…Congenital partial or complete coronary ostial stenosis or atresia (COSA), atherosclerosis (familial hyperlipidemia), Kawasaki disease, Takayasu aortitis, and syphilis are some of the causes for this rare condition [1][2][3][4][5][6][7][8]. In our patient, other than persistent elevation of ESR, no other abnormalities were found in the investigations suggestive of specific type of vasculitis.…”
Section: Discussionmentioning
confidence: 84%
“…Determining the exact nature and extent of the disease as well as the adequate expansion of the stent are some of the important technical consideration of the procedure in this patient. Intravascular ultrasound (IVUS) would have been extremely useful [7] in this situation but it was not performed as the facility was not available in our catheterization laboratory at that time. However, this type of urgent coronary intervention with DES may be lifesaving even without pre-procedural IVUS assessment in a resources poor setting.…”
Section: Discussionmentioning
confidence: 99%